Praktek Jual Beli Paket Data Internet dalam Perspektif Hukum Islam di Alya Ponsel Desa Sitimbaga Kecamatan Halongonan Timur - harahap, suciana (Taushiah: Jurnal Hukum, Pendidikan dan Kemasyarakatan, 2023)
In the practice of buying and selling the active period of data packages, the buyer comes directly to that place. After finding the internet data package you want to use, then buy it and make a transaction. The data package purchased was the Telkomsel internet data package, the seller said that the contents of the package were 30 GB and the active period on the starter card was 2 months and Indosat 3 GB with an active period of 1 month as stated on the packaging. The seller and buyer have made an agreement and then consent and qabul occur at that place. The buyer gives money worth the goods and the seller gives the goods that have been agreed upon between the seller and the buyer at one time at that place. In the analysis of Islamic law, the first thing to do in the buying and selling process is to fulfill the applicable requirements, including the existence of a seller and a buyer, the object of the sale and purchase, there is a medium of exchange, the sale and purchase is carried out directly on the spot, there is an agreement between the seller and the buyer. This research is field research which is descriptive-analytic in nature. The research object and location is the Alya cellphone in Sitimbaga Village, East Halongonan District with a normative Islamic business research approach which aims to find answers in the form of Islamic business rules regarding buying and selling internet data quota packages. The data collection techniques used are interviews and documentation, the techniques for drawing conclusions are data reduction, data presentation, and drawing conclusions. The results of this research show that there is an element of gharar (deception), a mismatch between the active period of internet data packages and the agreement that has been made, causing harm to one of the parties.